A SYNTHESIS KEYNES-MONETARIST AND REAL BUSINESS CYCLE MODEL TO INFLATION AND UNEMPLOYMENT IN INDONESIA 2000.1-2014.4 - Aris Soelistyo (Faculty of Economics and Business, University of Muhammadiyah Malang, 2017)
This research is addressed for the construction of Synthesis between Keynesian, Monetarist and Real Business Cycle Model to the inflation and unemployment Data is used quarterly data 2000.1 - 2014.4, The result of this research with the Keynesian model is the aggregate demand gap has no significance effect to inflation rate and the unemployment rate. But when model of variable input mount the unemployment, exchange rate, wage and the aggregate demand gap of hence yielding elastic inflation elasticity finding of positive of equal to 2,48 to the unemployment rate, and the inflation elasticity to foreign exchange is inelastic positive significance of equal to 0,88. As for the influence of wages to inflation is significantly negative elastic of equal to – 1,89. Besides, in model is also shown by condition of significance of influence of variable of aggregate demand gap to inflation of equal to 0.31. Meanwhile, Inflation in perspective monetarist viewed as by a monetary phenomenon, where the inflation influenced by money supply of equal to 1.858. Besides, Monetarist also express of relation significance of between GDP summed ugly is money supply is inelastic positive significance of equal to 0.1247. The RBC Model shows that the investment elasticity to output is significance inelastic positive equal to 0.405467, that way also with the influence of the population to GDP is significance negative equal to - 1.259925 . The other side, is founded by of Unemployment elasticity to wage rate is significance positive of equal to 0.413. Meanwhile, with the model of synthesis Keynes-Monetarist and RBC lay open that output (GDP) is influenced by the positive significance of equal to 0.206026 . The synthesis model is also expressed by that governmental fiscal governmental expenditure as a means of shows influence which significant to unemployment equal to 0.149. While component amount of money supply, affecting negativity significance to unemployment of equal to 0.55887.